Immunogenicity of coronavirus disease 2019 vaccines in children: A review with ChatGPT - Daniel Leung; Jaime Rosa Duque; Wenwei Tu; Yu Lung Lau (Pediatric Discovery)
Abstract SARS‐CoV‐2 causes millions of infection cases and coronavirus disease 2019 (COVID‐19)‐related deaths worldwide. In addition to acute illnesses, children and adolescents suffer from post‐infectious complications. Vaccination is a promising preventative treatment that can confer protection from these devastating outcomes. Utilizing ChatGPT, this review discusses the immunogenicity of mRNA and inactivated COVID‐19 vaccines in children and adolescents. Rapid vaccine discovery during the COVID‐19 pandemic led to the approval of the mRNA vaccines that stimulate potent antibody responses in pediatric population, and the younger age groups develop higher neutralizing and non‐neutralizing antibody responses than those who are older. Natural infection induces weaker antibody responses than vaccination. Vaccine‐induced humoral immunity decreases over time, as antibodies decline six months after the second dose. However, antibody avidity increases, which partly maintains neutralization and Fc‐effector functions that provide more durable protection. Inactivated COVID‐19 vaccines generate strong antibody responses in children and adolescents. They induce T cell responses against multiple structural protein antigens, although their neutralizing antibody responses appear weaker and wane more quickly than mRNA vaccines. Full‐dose intradermal administration and heterologous prime‐boost may improve the immunogenicity of inactivated vaccines. In children and adolescents, immune protection from the pre‐Omicron variants of concern (VOCs) is maintained. Vaccination induces less antibody neutralization against the Omicron variant, but non‐neutralizing antibodies and T cell responses persist. Hybrid immunity provides stronger immunogenicity against SARS‐CoV‐2 in the pediatric population. Future research must focus on long‐term immunity, interaction with breakthrough reinfections, cross‐reactivity against new VOCs, T cell immunogenicity and immunogenicity in young children.